Faktor Risiko Kejadian Kanker Serviks di RSU Kertha Usada Buleleng - Putu Indah Sintya Dewi; Aditha Angga Pratama; Ni Made Dwi Yunica Astriani (ARTERI : Jurnal Ilmu Kesehatan, 2023)
Cervical cancer is a silent killer for a woman. Most women infected with cervical cancer are known or come to health services after entering an advanced stage. This study goal was to analyze the risk factors for cervical cancer at Kertha Usada Public Hospital. The research method uses quantitative research with a case control approach. The independent variables of the study were characteristics (mother's age, age of marriage, education, occupation, parity), history of contraceptive use, length of use of contraception. While the dependent variable is the incidence of cervical cancer. The research data uses secondary data from 2020-2022 and is collected using data extract sheets. After the data was collected, it was analyzed using univariate, bivariate using chi square and multivariate using logistic regression. The results of the study found that the risk factor for cervical cancer was young marriage (AOR: 4.9, 95% CI 2.04-11.8). Then history of use of hormonal contraception (AOR: 3.01, 95% 1.3-6.9). In conclusion, there are 2 risk factors for cervical cancer at Kertha Usada General Hospital, namely young age of marriage and use of hormonal contraception.